The Effect of Probiotics on Headaches in Children with Migraine Treated with Sodium Valproate A Randomized Controlled Clinical Trial - Bidabadi, Elham; Elyasi, Mitra; Hassanzadeh Rad, Afagh; Kazemnezhad, Ehsan (Iranian Journal of Child Neurology, 2023)
Objective Migraine is one of the most common complaints in children. This study aimed to determine the effect of probiotics (KidiLact) on headaches in children aged six to 15 years with migraine treated with sodium valproate. Materials & Methods This double-blind, randomized controlled clinical trial was performed on eighty children with migraine treated with sodium valproate. Patients were divided into two groups. All patients in the intervention and control groups received two sachets of probiotics and a placebo daily for four months, respectively. They were compared in terms of frequency and severity of headaches and painkiller consumption before and two and four months after initiating probiotics. Results The mean number of headaches in the second and third visits in the probiotic group was 1.27 and 1.18, and 2 and 1.50 per month in the placebo group, respectively. The authors observed a significant difference between the two groups in the second (P = 0.010) and the third visit (P = 0.019). Moreover, the mean severity of headache in the second and third visits in the probiotic group was 1.38 and 1.23, and 1.60 and 1.53 in the placebo group, respectively. The authors demonstrated that the daily consumption of painkillers in the probiotic group was significantly reduced compared to the placebo Received: 23-Des-2022 group (P = 0.007). Conclusion Using probiotic supplements seems to significantly affect the severity and frequency of migraine headaches compared to the placebo, and daily consumption of painkillers was significantly reduced in the probiotic group compared to the placebo group